Survival Analysis of Ovarian Carcinosarcomas Depending on Platinum or Doxorubicin Based Adjuvant Chemotherapy - İlker Selçuk; İpek Düzgüner; Sevda Baş; Taner Turan; Afra Alkan; Nurettin Boran; Mehmet Mutlu Meydanlı; Gökhan Tulunay (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To analyse the survival outcomes of women with ovarian carcinosarcoma according to platinum or doxorubicin based adjuvant chemotherapy protocols.